Enhancing Job Performance through Islamic Religiosity and Islamic Work Ethics - Zahrah, Novia; Hamid, Siti Norasyikin Abdul; Rani, Shamsul Huda Abdul; Kamil, Bidayatul Akmal Mustafa (International Review of Management and Marketing, 2016)
Numerous researches on the influence of Islamic work ethics on job performance have been conducted. However, few studies have considered Islamic religiosity at the workplace in affecting job performance. Thus, this study is conducted to fill the gap by investigating the role of Islamic work ethics and Islamic religiosity on job performance of Muslim employees. Data were collected from 150 administrative employees in higher educational institutions in Malaysia. The data were later analyzed using partial least square method using the Smart-PLS software. Results indicate that Islamic religiosity and Islamic work ethics were found to be significantly associated with job performance. Implications of the study for managers and suggestions for future research are presented. Keywords: Job Performance, Islamic Religiosity, Islamic Work Ethics JEL Classifications: J29, L25, M140, N350, Z120